Didactic strategies of the seven knowledge of Edgar Morin in environmental education learning - Carlos Ramos, José Alberto (2019)
The general objective of the study was to determine the effect of the didactic strategies of the teacher based on the paradigm of the seven knowledge of Edgar Morín, in the learning of environmental education, in students of the Higher Institute of Public Technological Education Santos Villalobos Huamán Region Cajamarca Peru. The focus of quantitative research, quasi-experimental design; the sample consisted of 20 students (10 from the control group and 10 from the experimental group); the instrument used was an environmental education exam, structured by 40 items, on the vigesimal scale; what allowed to evaluate the learning. The results of the investigation show that after using the paradigm of Edgar Morín in the experimental group of students, there were significant differences compared to the control group; also descriptively the means of the notes of the experimental group, were higher in the learning variable and in each of the seven knowledge.